2020
DOI: 10.2147/cia.s244910
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predictive Value of Nutritional Risk Screening 2002 and Mini Nutritional Assessment Short Form in Mortality in Chinese Hospitalized Geriatric Patients</p>

Abstract: Background and Aim: The presence of malnutrition in hospitalized geriatric patients is associated with an increased risk of mortality. This study aimed to examine the performance of Nutritional Risk Screening 2002 (NRS2002) and Mini Nutritional Assessment Short Form (MNA-SF) in predicting mortality for hospitalized geriatric patients in China. Methods: A prospective analysis was performed in 536 hospitalized geriatric patients aged ≥65 years. Nutrition status was assessed using the MNA-SF and NRS2002 scales wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
2
8

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 28 publications
6
16
2
8
Order By: Relevance
“…Using the NRS-2002, Liu et al [46] identified an 85.1% prevalence of nutritional risk among elderly patients with COVID-19. This is higher than the prevalence recorded by Zhang et al [78], who also used the NRS-2002, but in a study that included 536 hospitalized patients with different diseases. Another study using the NRS-2002, included 114 Chinese with gastric cancer, a clinical condition that leads to severe catabolism, identified a 70.1% prevalence of nutritional risk [76], and a systematic review including studies of European patients hospitalized for various diseases found a prevalence of 41.5% [23].…”
Section: Discussioncontrasting
confidence: 54%
“…Using the NRS-2002, Liu et al [46] identified an 85.1% prevalence of nutritional risk among elderly patients with COVID-19. This is higher than the prevalence recorded by Zhang et al [78], who also used the NRS-2002, but in a study that included 536 hospitalized patients with different diseases. Another study using the NRS-2002, included 114 Chinese with gastric cancer, a clinical condition that leads to severe catabolism, identified a 70.1% prevalence of nutritional risk [76], and a systematic review including studies of European patients hospitalized for various diseases found a prevalence of 41.5% [23].…”
Section: Discussioncontrasting
confidence: 54%
“…Using the NRS-2002, Liu et al [ 46 ] identified an 85.1% prevalence of nutritional risk among older adults with COVID-19. This is higher than the prevalence recorded by Zhang et al [ 78 ], who also used the NRS-2002, but in a study that included 536 hospitalized patients with different diseases. Another study using the NRS-2002, included 114 Chinese with gastric cancer, a clinical condition that leads to severe catabolism, identified a 70.1% prevalence of nutritional risk [ 76 ], and a systematic review including studies of European patients hospitalized for various diseases found a prevalence of 41.5% [ 23 ].…”
Section: Discussionmentioning
confidence: 55%
“…In this cohort, we had studied that low CC could increase nutritional risk [ 16 ], and the malnutrition was an independent risk factor for mortality [ 22 ]. In addition, the Nutritional Risk Screening 2002 (NRS2002) score can independently predict the mortality compared with the Mini Nutritional Assessment Short Form (MNA-SF) over more than 2 years of follow-up [ 23 ]. In this study, we focused on the CC’s performance in frailty in this cohort.…”
Section: Methodsmentioning
confidence: 99%